Effects of a Traditional Rose-Based Polyherbal Formula ‎on Clinical Symptoms of Patients with Functional Dyspepsia: A Double-Blind Randomized Controlled Trial - Hossein Kerdarian; Seyed Hassan ‎ Abedi; Seyyed Ali Mozaffarpur; Hoda Shirafkan; Zahra Memariani (Tehran University of Medical Sciences, 2022)
Functional dyspepsia (FD) is a common gastroduodenal disorder that can be long-lasting. In the present study, we aimed to investigate the effect of herbal medicine, Ghors-e-Vard (Vard), on clinical symptoms in FD patients. Seventy adult FD patients according to the Rome IV criteria and without Helicobacter pylori infection were included. Participants were randomly allocated to either Vard or placebo group for 4 weeks of intervention. Treatments were given orally in a double-blind fashion (500 mg, three times a day, and half an hour after each meal). Patients were evaluated prior to and following 2, 4, and 8 weeks after the intervention, in terms of changes in the total score of gastrointestinal symptoms rating scale (GSRS), Depression Anxiety Stress Scales (DASS-21), scores of various components of the 36-item short-form health survey (SF-36), and any reported side effects. The differences of GSRS and DASS-21 total scores from baseline to the end of intervention were significantly larger in Vard group (P<0.001). Except for reflux, the other subtypes of FD symptoms were decreased with a significantly greater effect in Vard group (P < 0.05). Also, changes in the total score of SF-36 at 4 and 8 weeks after the intervention were significantly greater in Vard group (P<0.001). Except for the reflux, improvement of gastrointestinal symptoms, along with depression, stress, and anxiety, as well as the quality of life in Vard group, was significantly superior to the placebo group. These findings suggest that the Vard, as a complementary therapy, may have a promising effect on resolving the FD symptoms.